2022
DOI: 10.1177/07487304221103376
|View full text |Cite
|
Sign up to set email alerts
|

Sleep of Healthcare Workers During the COVID-19 Pandemic and the Role of Atypical Work Schedules: A Scoping Review

Abstract: The COVID-19 pandemic has negatively impacted the well-being of healthcare workers (HCWs). HCWs are highly exposed to shift work and their work schedules have been subject to increasing unpredictability since the start of the pandemic. This review aims to: (1) map the studies providing information about factors associated with sleep characteristics in HCWs working in the context of the COVID-19 pandemic during the first and second waves and (2) examine the state of the evidence base in terms of the availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…Perceived control over work is a key factor affecting workers' perception of work stress. Research suggested that during the COVID-19 pandemic, atypical work schedules such as shift work status and extended working hours may create greater uncertainty for the healthcare workers, which will affect their sleep (Power et al, 2022). We defined the multiple mediating effects of psychological capital and occupational stress on the relationship between perceived organizational support and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived control over work is a key factor affecting workers' perception of work stress. Research suggested that during the COVID-19 pandemic, atypical work schedules such as shift work status and extended working hours may create greater uncertainty for the healthcare workers, which will affect their sleep (Power et al, 2022). We defined the multiple mediating effects of psychological capital and occupational stress on the relationship between perceived organizational support and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-Objective Optimization: The methodology employs a multi-objective optimization approach, which has been applied to a variety of construction projects [ 50 , 57 , 58 , 59 ] [ 47 , 48 , 49 , 50 ], to find a set of non-dominated solutions that form the Pareto frontier [ 61 , 62 ]. Then, a set of solutions belonging to the feasible region are determined [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…Others designed a multi-objective mixed integer linear programming model to design a sustainable closed-loop supply chain network of face masks during the COVID [ 46 ]. Power et al [ 47 ] developed a study on healthcare workers by mapping the studies about factors associated with sleep characteristics in this type of employees working during the pandemic and then examining the availability of information on the influence of atypical work schedules. Lehnig et at.…”
Section: Introductionmentioning
confidence: 99%
“…Combined consideration of both occupational characteristics of healthcare professionals ( 23 , 30 , 42 ) [e.g. atypical work schedules ( 43 ), heavy workload and stress ( 44 )] and lifestyle behaviors which have been identified as potential factors affecting HRQoL in the Chinese population ( 39 , 45 47 ), lifestyle behaviors including daily routine, breakfast, sleep quality, smoking, drinking and physical activity should be taken into account. The absence of relative research on the relationship between such lifestyle behaviors and HRQoL among PHC physicians, however, is an impediment to health policy consideration for improving their HRQoL.…”
Section: Introductionmentioning
confidence: 99%